Hubungan Kepemimpinan Kepala Sekolah dan Kinerja Guru dengan Karakter Siswa Berbasis Budaya Lokal - Dodi Ilham; Nurdin Kaso; Nurul Aswar Aswar; Nurhasanah R (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2021)
This study aims to determine: the relationship between the principal's leadership and teacher performance, the relationship between the principal's leadership and the student's character based on local culture, the relationship between the teacher's performance and the student's character based on the local culture, and the relationship between the principal's leadership and the student's character based on local culture through teacher performance. This research is a quantitative research with a correlational design. The research approach is a managerial, pedagogical, sociological, and psychological approach. The data collection instruments used were questionnaires, observation guidelines, interviews, and documentation. Research data analysis is by using editing, coding, and tabulating. The results of data analysis show that there is a significant influence of principal leadership with teacher performance, principal leadership with student character based on local culture, teacher performance with student character, and principal leadership with student character based on local culture through teacher performance with a significance value of 0.000 0.05 which means Ha is accepted and Ho is rejected. The results of the data are significant: there is a significant relationship between the principal's leadership variable and teacher performance; there is a significant relationship between the principal's leadership variable and the student's character; There is a significant relationship between the teacher's performance variable and the student's character; there is a relationship between the principal's leadership variable and the student's character through teacher performance.